Is perception the canonical route to aesthetic judgement? - Robson, Jon (Taylor & Francis, 2018)
It is commonplace amongst philosophers of art to make claims which postulate important links between aesthetics and perception. In this paper, I focus on one such claim: that perception is the canonical route to aesthetic judgement. I consider a range of prima facie plausible interpretations of this claim and argue that they each fail to identify any important link between aesthetic judgement and perception. Given this, I conclude that we have good reason to be sceptical of the claim that perception is in any way privileged as a source of aesthetic judgement.